EMPOWERING WOMEN TO ASSUME LEADERSHIP POSITIONS : EMPOWERING WOMEN TO ASSUME LEADERSHIP POSITIONS - Fitriani, Aida (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
Empowering women to occupy leadership positions is necessary because women have equal rights and opportunities as men to participate in development and governance, including in strategic positions. The government has established various policies and programs aimed at achieving gender equality and justice. However, in practice, these policies have not been fully implemented optimally. This condition is reflected in the low representation of women in leadership positions compared to men. Various efforts have been made to encourage the empowerment of female civil servants, one of which is by providing equal opportunities for women to occupy positions that were previously dominated by men. However, in percentage terms, the number of women in leadership positions is still relatively low. Therefore, women strive to improve their capacity through education and knowledge development, both formally and informally. In addition to improving their competence, women also strive to create a conducive, supportive work environment and develop their potential in carrying out their duties and responsibilities. Active participation in meetings and decision-making processes is an important part of these empowerment efforts. On the other hand, women are still faced with the dual roles of being workers and household managers, which often causes them to feel overwhelmed.